Fifty years of cave arthropod sampling: techniques and best practices - Wynne, J.; Howarth, Francis; Sommer, Stefan; Dickson, Brett (International journal of speleology, 2019)
Ever-increasing human pressures on cave biodiversity have amplified the need for systematic, repeatable, and intensive surveys of cave-dwelling arthropods to formulate evidence-based management decisions. We examined 110 papers (from 1967 to 2018) to: (i) understand how cave-dwelling invertebrates have been sampled; (ii) provide a summary of techniques most commonly applied and appropriateness of these techniques, and; (iii) make recommendations for sampling design improvement. Of the studies reviewed, over half (56) were biological inventories, 43 ecologically focused, seven were techniques papers, and four were conservation studies. Nearly one-half (48) of the papers applied systematic techniques. Few papers (24) provided enough information to repeat the study; of these, only 11 studies included cave maps. Most studies (56) used two or more techniques for sampling cave-dwelling invertebrates. Ten studies conducted >10 site visits per cave. The use of quantitative techniques was applied in 43 of the studies assessed. More than one-third (42) included some level of discussion on management. Future studies should employ a systematic study design, describe their methods in sufficient detail as to be repeatable, and apply multiple techniques and site visits. This level of effort and detail is required to obtain the most complete inventories, facilitate monitoring of sensitive cave arthropod populations, and make informed decisions regarding the management of cave habitats. We also identified naming inconsistencies of sampling techniques and provide recommendations towards standardization.